A imagem no livro didático de ensino religioso - Carlos, Dafiana do Socorro Soares Vicente (2015)
Prior to the invention of writing, the image was a means of communication which contributed to the expression of social relations, to the culture and ideology of the age. With the „development‟ of civilization, the image lost its natural character, which led to the configuration of a new system of symbols, from the ideogram to the rise of the alphabet, bringing about a break in the communication through images. However, with the advent of post-modernity and the advance of media culture a new concept has been established in society, a concept marked by the symbolic and by the proliferation of the image. Given the range of the theme „image‟ in the various fields of science, we delimit our analysis in terms of the religious imagination and the images contained in Teaching Manuals used in Religious Education (TMRE) from the platform of Gilbert Durand‟s symbolical hermeneutics. In this vein the research concentrated, initially, on enumerating certain theoretical presuppositions which guide and sustain the analysis undertaken with a view to strengthening its relevance in relation to the triad of the „religious imagination‟, the visual image and the teaching manual. The aim is to consolidate and collaborate with the development of research on religious symbolic representation, bearing in mind the thematic issue of the visual image in TMRE, in order to use it critically and creatively in educative spaces in schools. The findings of this research point to the guaranteed presence of the visual image in TMRE, above all in the genres of drawing, painting, photography and info-imagery, with the hegemony of photography. While the treatment of the image as an object of knowledge is outlined, therefore, as a codifier of religious symbolic representations, the predominant pedagogical use is illustrative. The general configuration of TMRE was structured on the basis of imaginary representation in the mystical-religious form, set within a theological and messianic conception of religion.